Prevalence of left atrial thrombus by real time three‐dimensional echocardiography in patients undergoing electrical cardioversion of atrial fibrillation: A contemporary cohort study. Issue 4 (5th March 2021) - Bursi, Francesca; Santangelo, Gloria; Ferrante, Giulia; Massironi, Laura; Carugo, Stefano
Abstract: Background: The prevalence of left atrial thrombi in patients scheduled for electrical cardioversion (ECV) of atrial fibrillation (AF) remains unknown in contemporary real‐life practice. Methods and Results: Patients scheduled for ECV underwent transesophageal echocardiography (TEE) regardless of AF duration and type of anticoagulant. Of 277 consecutive patients (65% men, mean age 71 ± 10 years, CHA2 DS2 ‐VASc 3.1 ± 1.4), 92 were on direct oral anticoagulants (DOACs) and 99 on antivitamin K (AVK) oral agents for at least 3 weeks before and 4 after ECV. Eighty‐five patients with paroxysmal AF on low‐molecular‐weight heparin were also considered. Real time three‐dimensional TEE detected left atrial appendage (LAA) thrombus in 7% of patients, without significant difference among three groups ( P = .334). Anticoagulation was ineffective in eight patients on AVK oral agents, two of them had thrombus. Eight patients assumed incorrectly DOACs, four of them had thrombus. Among the 175 patients on effective anticoagulation, five showed thrombus, three on AVK oral agents, and two on DOACs ( P = .716). Effective anticoagulation was associated with reduced risk of thrombosis (OR: 0.16, 95%CI: 0.06‐0.45, P = .001). In patients with correct anticoagulation, predictors of thrombus were CHA2 DS2 VASc (for each point of increment OR: 1.97, 95%CI: 1.08‐3.61, P = .029), low left ventricular ejection fraction (OR: 0.92, 95%CI: 0.86‐0.99, P = .026), and degree of spontaneous echo‐contrast (for each point increase OR: 10, 95%CI: 2‐39, P < .0001). Conclusion: Patients with AF, on effective anticoagulation, had a prevalence of thrombus not negligible regardless of type of anticoagulant. TEE is prudent before ECV and mandatory if unsuccessful anticoagulation is proved or suspected.